Exploring the Pharmacological Mechanism of Radix Salvia Miltiorrhizae in the Treatment of Radiation Pneumonia by Using Network Pharmacology - Li, Peng; Xia, Xiaochun; Zhou, Jundong; Wu, Jinchang (Frontiers in Oncology, 2021)
Background: Radiation pneumonia (RP) is the most common complication of radiotherapy to the thorax and seriously affects the survival rate and quality of life of patients. Radix Salviae Miltiorrhizae (RSM) is an ancient Chinese medicine, whose main pharmacological effect is to promote blood circulation and remove stasis. A growing number of studies have proved that RSM has a good effect on RP. However, the underlying mechanism is still unclear and needs to be fully elucidated. Methods: The effective components and predictive targets of RSM were analyzed by Traditional Chinese Medicine Systems Pharmacology (TCMSP) database, and the related targets of RP were predicted by GeneCards database. The common targets of the two targets mentioned above were analyzed by Protein-protein interaction on the STRING website, GO and KEGG analysis on the DAVID website, visualization by CytoScape3.7.0 and screening for Hubber gene by cytoHubber plug-in. Results: A search of the TCMSP database revealed that RSM contains 65 chemical constituents and 165 potential protein targets.2162 protein targets were found to be associated with RP. The top 10 hub genes were obtained by MCC algorithm for 70 common genes, including TP53, CASP3, MAPK1, JUN, VEGFA, STAT3, PTGS2, IL6, AKT1 and FOS. By analyzing the GO, RSM may in the nucleus (CC) by positive regulation of transcription from RNA polymerase II promoter (BP), Extrinsic apoptotic signaling pathway in absence of ligand (BP) and lipopolysaccharide – mediated Signaling pathway (BP) plays the role of Protein homodimerization activity (MF) to play the role of anti-radiation pneumonia. Three possible signaling pathways (PI3K-AKT, HIF-1, TNF) could be the underlying mechanism of RSM. Conclusions: Through network pharmacology analysis, we found the possible target genes of RSM on RP, and revealed the most likely signaling pathway, providing theoretical basis for further elucidating the potential mechanism of RSM on RP.